Whole-genome sequencing of multiple related individuals with type 2 diabetes reveals an atypical likely pathogenic mutation in the PAX6 gene - Boehm, Bernhard Otto (2023)
Pathogenic variants in more than 14 genes have been implicated in monogenic diabetes; however, a significant fraction of individuals with young-onset diabetes and a strong family history of diabetes have unknown genetic etiology. To identify novel pathogenic alleles for monogenic diabetes, we performed whole-genome sequencing (WGS) on four related individuals with type 2 diabetes - including one individual diagnosed at the age of 31 years - that were negative for mutations in known monogenic diabetes genes. The individuals were ascertained from a large case-control study and had a multi-generation family history of diabetes. Identity-by-descent (IBD) analysis revealed that the four individuals represent two sib-pairs that are third-degree relatives. A novel missense mutation (p.P81S) in the PAX6 gene was one of eight rare coding variants across the genome shared IBD by all individuals and was inherited from affected mothers in both sib-pairs. The mutation affects a highly conserved amino acid located in the paired-domain of PAX6 - a hotspot for missense mutations that cause aniridia and other eye abnormalities. However, no eye-related phenotype was observed in any individual. The well-established functional role of PAX6 in glucose-induced insulin secretion and the co-segregation of diabetes in families with aniridia provide compelling support for the pathogenicity of this mutation for diabetes. The mutation could be classified as "likely pathogenic" with a posterior probability of 0.975 according to the ACMG/AMP guidelines. This is the first PAX6 missense mutation that is likely pathogenic for autosomal-dominant adult-onset diabetes without eye abnormalities.